THE EFFECTIVENESS OF VIRTUAL REALITY OF THE YOUTH PLEDGE MUSEUM TO INCREASE THE HISTORICAL AWARENESS OF CLASS XI SENIOR HIGH SCHOOL STUDENTS - Bahroni, Agung; Setiawan, Risky; Fitrianti, Vionita Vara; Nugroho, Alifi Nur Prasetia (Universitas Labuhanbatu, 2024)
This study aims to assess how much of the Youth Pledge Museum’s Virtual Reality can improve historical understanding in grade XI students in high school. The approach used in this study was an experimental method with a One Group Pretest Posttest design, involving 68 grade XI students from SMA Negeri 1 Jepara as participants. Data collection was carried out with an instrument in the form of a historical awareness questionnaire given at the pretest and posttest stages. Data were analyzed using the T-Test and N-Gain Test to measure the effectiveness of using the Youth Pledge Museum's Virtual Reality in increasing students' historical awareness. The study results were based on the Independent Sample T-Test, which obtained a sig value. 0.000 <0.050, which means that using of the Youth Pledge Museum’s Virtual Reality affects students' historical awareness. This is supported by the results of the N Gain Test, which obtained a score of g (0.88) > 0.71, which means that the impact of using of the Youth Pledge Museum’s Virtual Reality on the historical awareness of students in the “High” category. The conclusion from the study results is that the Youth Pledge Museum’s Virtual Reality has effectively increased the historical awareness of grade XI students in Senior High School.